Biological – Psychophysical and Aesthetic Categories for Space Modeling - -, Elena Nikoljski Panevski; -, Umnije Aziri; -, Zejnelabedin Aziri (International Journal for Multidisciplinary Research (IJFMR), 2024)
The main goals of the research in this paper are to explain the role of biological - psychophysical and aesthetic in the conceptualization of the architectural space. Research in this direction has been and still is a constant focus of researchers, and in this way, it grows from an initiation into a basis for application in everyday architectural practice. The only possible orientation in this case is interdisciplinary – the use of fundamental knowledge and new research from the fields of human sciences, such as psychology, aesthetics and others. Exploring the architectural space modeling categories, we examine all scientific disciplines that directly and indirectly influence design, planning, design, but also the experience of space as essential parameters in architectural theory and practice.
Keywords: Architectural space; interiors; modeling levels; biological level; psychophysical level; aesthetic categories.